Synthesis and Structure of Cadmium Complex {[Cd(adi)0.5Cl(bimt)]·H2O}n - Zhang, Jiao-Lin; Hao, Bao-Lian; Yang, Huai-Xia (Asian Journal of Chemistry, 2015)
The cadmium complex {[Cd(adi)0.5Cl(bimt)]·H2O}n (H2adi = adipic acid, bimt = 2-((benzoimidazol-yl)methyl)-1H-tetrazole) was prepared by reaction of CdCl2·2.5H2O, bimt and H2adip in methanol/water solution and its structure was determined by single crystal X-ray diffraction analysis. The crystals are triclinic, space group P-1 with a = 8.4863(17) Å, b = 8.5551(17) Å, c = 11.422(2) Å, a = 100.08(3)º, b = 106.33(3)º, g = 98.37(3)°, V = 766.7(3) Å3, Z = 2, F(000) = 434, Dc = 1.898 g/cm3, μ = 1.623 cm-1, the final R = 0.0252 and wR = 0.0566. A total of 8672 reflections were collected, of which 3584 were independent (Rint = 0.0216).